Evaluation of Acetylcholinesterase Biosensor Based on Carbon Nanotube Paste in the Determination of Chlorphenvinphos - A. C. Oliveira; L. H. Mascaro (International Journal of Analytical Chemistry)
An amperometric biosensor for chlorphenvinphos (organophosphorus pesticide) based on carbon nanotube paste and acetylcholinesterase enzyme (CNTs-AChE biosensor) is described herein. This CNTs-AChE biosensor was characterized by scanning electron microscopy (SEM) and electrochemical impedance spectroscopy (EIS). The SEM result shows the presence of CNTs and small lumps, due to the enzyme AChE, which has a type of cauliflower formation. From EIS analysis is possible to observe increased Rtc for CNTs-AChE biosensor when compared to the carbon nanotube paste electrode for the reaction [Fe(CN)6]4−/3−. Using a chronoamperometric procedure, a linear analytical curve was observed in the 4.90×10-7–7.46×10-6 M range with limit of detection of 1.15×10−7 M. The determination of chlorphenvinphos in the insecticide sample proved to be in agreement with the standard spectrophotometric method, with a 95% confidence level and with a relative error lower than 3%. In this way, the CNTs-AChE biosensor presented easy preparation, fast response, sensitivity, durability, good repeatability, and reproducibility.